COMBINED EFFECT OF GROWTH HORMONES AND GYPSUM INDUCES SALINITY TOLERANCE IN WHEAT UNDER SALINE-SODIC SOIL - K. Ahmed; G. Qadir; M. Q. Nawaz; M. A. Riaz; M. F. Nawaz; M. M. A. Ullah (Journal of Animal and Plant Sciences, 2020)
In recent decades effective regulatory role of phytohormones in plants in response to salinity has received considerable attention. However, their role acting in combination with gypsum still remain elusive. That is why, this two-year study was conducted to assess the effects of foliar application of salicylic acid and L-tryptophan with and without gypsum on wheat crop in a moderately salt affected soil with ECe: 4.71 dS m-1, pHs: 9.18 and SAR: 31.82. Treatments detail is as under: - (A). Amendments 1: gypsum @ 50% GR, 2: without gypsum, (B). Plant hormones T1: control, T2: SA @10-5 M, T3: L-TRP @10-5 M, T4: SA + L-TRP (each @10-5 M in 1:1). Results indicated that growth and yield parameters were higher in T4 (SA+L-TRP @ 10-5 M in 1:1 ratio) with gypsum application @ 50% of GR. Individual application of either salicylic acid (SA) or L-tryptophan (L-TRP) improved the yield in comparison to control but the effect was more remarkable with their combined application. Post-harvest soil analysis clearly demonstrated that gypsum application improved the physical and chemical properties when compared to without application of gypsum. Results highlighted that salinity tolerance of wheat crop was increased in most of the studied parameters when these plant hormones were applied in combination, indicating a positive interaction between salicylic acid and L-tryptophan in salinized conditions.
Keywords: Abiotic stress. growth enhancer; cereal; soil quality